Madrasah Mu'allimin-Mu'allimat Curriculum Integration Sunan Drajat Lamongan Islamic Boarding School : Implementation of articles 17 and 18, Law No. 18 of 2019 - R. Zainul Mustafa; Siti Aminah (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
In 2007, the President of the Republic of Indonesia issued a government regulation on the implementation of religious education which recognizes that this type of Islamic education has made a great contribution to national development. The regulation explains that religious education such as Islamic boarding schools can be managed formally. Following the government regulation, the Minister of Religion then issued a Ministerial Regulation in 2014 to officially recognize pesantren as a traditional-based education. The regulation allows for the integration of yellow book-based education that allocates 70% or more of the curriculum to Islamic studies and Arabic, while 30% to general subjects. The formalization process of traditional Islamic education reached its peak with the passage of Law No. 18 of 2019 concerning Islamic boarding schools which was ratified on September 24, 2019. The pesantren system must be modernized and run classrooms under the madrasah system. On the other hand, the 2019 law recognizes many aspects of traditional pesantren traditions, including those that advocate the study of the yellow book. According to the law, the government is currently responsible for supporting the implementation of Islamic boarding school tradition-based education as well as support for public schools and madrasas. One of the Islamic boarding school educational institutions that has implemented the Islamic boarding school law is the Sunan Drajat Islamic Boarding School. Sunan Drajat Heritage Islamic Boarding School, one of the nine guardians, since 1994 has established a Mu'allimin-Mu'allimat institution whose curriculum has integrated the pesantren curriculum with the general education curriculum.